Aortic Cannulation around Grade 5 Aortic Arch Atheroma Utilizing Transesophageal Echocardiography - Trey W. Vanek; Jeremiah Hayanga; Matthew Ellison; Jeffrey Puette; Lawrence Wei; Heather K. Hayanga (Case Reports in Anesthesiology)
A 61-year-old male with severe aortic valve stenosis was scheduled for a minimally invasive bioprosthetic aortic valve replacement. Intraoperative transesophageal echocardiography (TEE) showed a unicuspid aortic valve and extensive aortic atheromatous disease. A large atheroma with mobile components existed near the distal aortic arch. A 17-French aortic cannula was successfully placed using TEE guidance with the tip proximal to the mobile atheroma to avoid inadvertent disruption and subsequent embolic sequelae. The patient had no evidence of perioperative stroke or other complications postoperatively. This case demonstrates one strategy to manage severe atheromatous disease intraoperatively. We also review additional management options.